An exploration of the coping mechanisms of caregivers of persons diagnosed with severe mental illness, in the Western Cape, South Africa - Hogan, Lynne (Department of Social Development, 2016)
This exploratory study on the coping mechanisms of caregivers in the Western Cape was undertaken in order to gain a better understanding of what caregivers experience and utilise in order to cope with their role as caregivers. Informal caregivers are the primary carers for people with a severe mental illness living within communities. They often carry a significant burden in this role and have many stresses which they need to deal with. It is therefore essential that a better understanding of their experience is gained in order to provide relevant support services and interventions. Hopefully the insights gained in this study will contribute to the formation of policies and interventions for caregivers which are appropriate and lead to further research in this field. This study was a qualitative study, conducted with 18 caregivers who participated in in-depth interviews. The results show that there is a large variety of both positive and negative coping mechanisms which caregivers employ dealing with the challenges and stresses they face. Positive coping mechanisms ranged from: making use of services and facilities available, working or keeping busy, knowledge of mental illness, support from family and friends, faith, finding the right doctor for the mentally ill person, support from hospital or clinic staff, looking after self and using challenges to grow, having lots of patience, taking one day at a time and listening to others' stories. Some of the negative coping mechanisms were: ignoring the mentally ill person or cutting off emotions, taking on all responsibility for the mentally ill person or controlling them, using verbal threats or abuse, isolating themselves and using medication to cope. The carers interviewed were also able to identify and access a number of social support mechanisms and systems available to them. Some of these provided psychological and emotional support, others provided physical / practical help and many provided both. The predominant social support mechanisms and systems were: hospitals and clinics, family and friends, churches and faith, support groups, Cape Mental Health and various NGOs. Participants in the study spoke about challenges and barriers in their role as carers. The research indicates that there are two main divides: challenges tend to be concerned with the person they are caring for while barriers tend to be external factors which carers have to deal with. Common challenges which carers face are: drug or alcohol use by the mentally ill person, unpredictable and disturbed thinking and behaviour, issues with medication and non-compliance, lack of person's insight, isolation and withdrawal from family life, lack of understanding from family and friends, financial problems. Barriers which are more external to the family unit include: lack of adequate medical services and facilities for the mentally ill person, lack of support services for the carer, lack of suitable accommodation for mentally ill people, carers not included in the treatment team and plan, police not helpful when asked for assistance with a mentally ill person, negative perceptions of mental illness in society. Recommendations of the study are for further research in this field; that mental health care services provide more support and interventions for caregivers; and that clear policies are developed and implemented for caregivers.